GIS-modellering av habitat för vitryggig hackspett (Dendrocopos leucotos) som hjälpmedel i naturvårdsplanering på landskapsnivå - Hoas, Linnea (SLU/Dept. of Ecology, 2008)
The white-backed woodpecker is a forest bird being critically endangered in Sweden. The species is dependent on older forests rich in deciduous trees and dead wood. The main problem for the survival of this species is present shortage of habitat. Conservation work on this umbrella species is at present focused on finding remaining or emerging habitat networks. Large areas are scrutinized in search for suitable habitats to be protected or managed for the species sake. These explorations are usually based on studying aerial photographs and habitat assessments in the field - the methods requiring large time investments since the species is area-demanding organism. Therefore, there is a need for developing a more cost-efficient methods that cover large areas. The method would need to be precise and furthermore consider long-term planning and development areas. Also, the spatial distribution of habitat ought to be analysed from the species perspective. Here, I investigate the usefulness of habitat suitability models based on ecological requirements of the species. This is performed in GIS environment using available geographic databases describing forests. The results of GIS modelling were compared to areas chosen by an ornithologist who has studied a part of the study area in the field. Forests development according to three different management scenarios was modelled for the coming 30 years. The results showed that GIS modelling with kNN estimations of forest variables and GSD-Land and Vegetation Cover (Svensk Marktäckedata) could find habitat areas equivalent to those habitats found in the field. GIS-map modelling offers good adaptation capacity as a planning tool in large-scale nature conservation work. The results also showed that forests of high conservation value that have been identified in Woodland Key Habitat scheme have relatively low importance for the white-backed woodpecker since they cover very small area in the studied region. This indicates that more efforts in creating habitats for the white-backed woodpecker are needed in the managed matrix. I conclude that GIS-modelling could be an important component in the conservation work for the white-backed woodpecker and other species that require large territories. Moreover, GIS-modelling offer the possibility to make forecasts for the future, something of great value when planning long-term nature conservation measures.